A new species of Alsodes (Anura: Alsodidae) from Altos de Cantillana, central Chile - Charrier, Andrés; Correa, Claudio; Castro, Camila; Méndez, Marco A. (Zootaxa, 2015)
Based on morphological and molecular evidence (mitochondrial and nuclear sequences) we describe a new species of spiny-chest frog, Alsodes cantillanensis, from central Chile (around 34°S). The type locality, Quebrada Infiernillo, is located in the Coastal Range at approximately 65 km from Santiago (Metropolitan Region), the capital of Chile. The distribution of the new species is included entirely in that of A. nodosus (32–36°S approximately), which was identified as the sister taxon according to molecular phylogenetic analyses. Moreover, both species are sympatric in the type locality. The new species was found in a Nothofagus macrocarpa relict forest potentially threatened by gold mining activities. We identify other threats for its conservation and some biological data needed for understanding the evolution of this species. This discovery reveals the scarce knowledge about biogeography, evolution and ecology of spiny-chest frogs from central Chile.